PENGARUH TINGKAT KECUKUPAN MODAL DAN DANA PIHAK KETIGA TERHADAP PEMBIAYAAN BERBASIS BAGI HASIL - Riyan Bagus Kristada; Ani Kusumaningsih (EkoPreneur, 2019)
The research examined influence of the level of capital adequacy and the third party funds to the profit based financing. This study uses Sharia Banks listed on the Financial Services Authority during the period 2013-2017 as the object of research. The research used quantitative. Source of data used is secondary data. Population of the research is Sharia Banks listed on the Financial Services Authority during the period 2013-2017. Determination of this research sample using purposive sampling method and obtained 5 Sharia Banks as samples. Technical data analysis used in this research is descriptive statistic test, classical assumption test, multiple linear regression analysis and hypothesis test using SPSS version 22.  The research showed that: the level of capital adequacy has a significant positive to the profit based financing, the third party funds has a significant positive to the profit based financing. And also the level of capital adequacy and the third party funds has a significant effect to the profit based financing. Keywords: The Level of Capital Adequacy, Third Party Funds, The Profit Based Financing.